Perlindungan Hak Kekayaan Intelektual di Era Digital: Studi Kasus Sengketa Merek PS Glow dan MS Glow - Amira Atsil Abigael Wegni; Novi Wulan Suci; Ulfa Kurnia Sari; Tabina Belinda Putri; Citra Hayu Khatintri (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The dispute over a brand involving MS Glow and PS Glow in 2023 is a trademark dispute that occurs due to similarities in the name of the trademark with another brand, so it is also called a copy of another trademark that has been registered with the Directorate General of Intellectual Property, so it can be said violates the first to file principle. In connection with this, this article examines the ongoing dispute between MS Glow and PS Glow in a complex and in-depth manner regarding the dispute resolution process related to the use of trademarks and forms of legal protection for PS Glow which are reviewed using the system followed by the Indonesian state. to files. This research is included in normative juridical research carried out through a statutory regulation approach. The findings of this study indicated that mediation was not a successful resolution method, so efforts continued through an arbitration body. Through arbitration, MS Glow has been proven to have committed brand infringement and paid damages to PS Glow. The first to file principle in trademarks stipulates that the first trademark registration has priority, and the importance of registering a trademark in accordance with the relevant product class is to prevent related legal disputes. The trademark dispute case between MS Glow and PS Glow shows the importance of registering a trademark correctly and in accordance with regulations to guarantee exclusive rights to the trademark.